ENRICHING ENGLISH LANGUAGE SPOKEN OUTPUTS OF KINDERGARTNERS IN THAILAND - Jeffrey Dawala Wilang; Kemtong Sinwongsuwat (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2013)
This year is designated as Thailand's "English Speaking Year" with the aim of improving the communicative competence of Thais for the upcoming integration of the Association of Southeast Asian Nations (ASEAN) in 2015. The consistent low-level proficiency of the Thais in the English language has led to numerous curriculum revisions and developmental policies on the national level. Since the implementation of educational reforms in the country in 1998, there has still been little research on its impact in the classroom, specifically the kindergarten level. The review conducted on the contemporary national education curriculum for kindergarten education did not specifically mention benchmarks for the children's English language performance. However, the curriculum explicitly detailed thirty-six integrated lessons for an academic year. Thus, in the absence of specific learning standards for English language learning at the kindergarten level, this paper provides snapshots of children's spoken outputs and lessons to enrich kindergartners' English language proficiency in Thailand.